2021
DOI: 10.3390/jcm10215144
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Multifocality on the Recurrence of Papillary Thyroid Carcinoma

Abstract: The incidence of thyroid cancer has dramatically increased over the last few decades, and up to 60% of patients have multifocal tumors. However, the prognostic impact of multifocality in patients with papillary thyroid carcinoma (PTC) remains unestablished and controversial. We evaluate whether multifocality can predict the recurrence of PTC. A total of 1249 patients who underwent total thyroidectomy for PTC at the Ewha Medical Center between March 2012 and December 2019 were reviewed. In this study, multifoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 32 publications
0
22
1
Order By: Relevance
“…All of the 23 studies were hospital‐based studies. Two articles 18,31 only reported papillary thyroid microcarcinomas (in which the maximal diameters were less than 1 cm) and the rest reported PTC patients 14,22,32–49 . The eligible studies were retrospective cohorts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the 23 studies were hospital‐based studies. Two articles 18,31 only reported papillary thyroid microcarcinomas (in which the maximal diameters were less than 1 cm) and the rest reported PTC patients 14,22,32–49 . The eligible studies were retrospective cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…We used a fixed effect model to evaluate the risk of multifocality for lateral lymph node metastasis (LLNM) among four studies 33,40,48,49 . The analysis showed that there was a significant association between tumor multifocality and LLNM (RR 1.86, 95% CI 1.62–2.14, p < .001) (Figures 2 and 4B).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, compared with the thyroid lobectomy group, the total thyroidectomy group was also found to have a larger tumor size, a higher rate of microscopic ETE, and an increased risk of LN metastasis. As these high-risk features could affect the development of recurrence, propensity score matching was performed to minimize potential biases [ 21 ]. After adjusting for possible confounding factors, including tumor size, microscopic ETE, LN metastasis, and coexisting Hashimoto thyroiditis, our matched cohorts showed no difference in RFS between the total thyroidectomy and lobectomy groups.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of dichotomous data was performed by Pearson chi-squared tests. To minimize potential confounding effects and selection bias, we performed 3:1 propensity score matching [ 21 ]. We selected 4 factors that could affect the recurrence as follows: tumor size, microscopic ETE, LN metastasis, and coexisting Hashimoto thyroiditis.…”
Section: Methodsmentioning
confidence: 99%
“…TC ( 7 ), gender ( 8 ), TPO-Ab ( 9 ), Tg-Ab ( 10 ), CR, and TG all have involvement in thyroid diseases. For example, males have a higher risk of recurrence in patients with papillary thyroid carcinoma than females ( 11 ). Another study evaluated the associations between thyroid antibodies (TPO-Ab and Tg-Ab) and the risk of preterm delivery ( 12 ).…”
Section: Discussionmentioning
confidence: 99%